Transformation Of Islamic Philanthropy: Reconstructing Zakat, Rahn, And Waqf Contracts Toward Productive Islamic Social Finance - Musrini Muis; Hamzah Khaeriyah; Rahmawati Muin (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to explore the reconstruction of Zakat, Rahn (Sharia Pawn), and Wakaf contracts to transform Islamic philanthropy instruments from a social dimension to a business (productive) economic dimension. The main challenge in managing philanthropy today is the tendency for its use to remain charitable and limited to physical infrastructure, thus failing to optimally reduce economic disparities. This study uses a qualitative approach with descriptive-analytical methods through a functionalist lens, in which each contract is reviewed based on its function in solving the economic problems of the community. The results show that the synergy between social contracts (tabarru') and commercial contracts (tijarah), such as the use of Qardhul Hasan, Mudharabah, Musyarakah, and Ijarah, can create a sustainable productive economic model. Implementation models such as the Mustahik to Muzakki entrepreneurship program in zakat, Ar-Rum products in Rahn, and project financing through cash waqf have proven effective in mobilizing community funds into productive assets. In conclusion, professional governance and integration between philanthropic instruments are crucial in building a strong, independent, and inclusive Islamic economic ecosystem.